2016
DOI: 10.1007/s40620-015-0255-4
|View full text |Cite
|
Sign up to set email alerts
|

Acute kidney injury among ST elevation myocardial infarction patients treated by primary percutaneous coronary intervention: a multifactorial entity

Abstract: Acute kidney injury is a frequent complication among ST segment elevation myocardial infarction (STEMI) patients undergoing primary percutaneous coronary intervention (PCI), and is associated with adverse outcomes. While contrast nephropathy is considered the most important reason for worsening of renal function, recent data have suggested the role of other important factors among this specific patient population. In the present review, we examine the various factors leading to renal impairment in STEMI patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
59
3
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(77 citation statements)
references
References 64 publications
11
59
3
4
Order By: Relevance
“…In addition, the AUROC for both of these scores to predict CIN when applied to patients with STEMI was 0.57 [14] which is much lower than the performance of our score. Most importantly, AKI in the setting of myocardial infarction is multifactorial and should not be assumed to be solely a contrast-induced nephropathy, as demonstrated by Shacham et al [5,6]. Therefore, the use of these scores cannot be extended to predict AKI in AMI patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the AUROC for both of these scores to predict CIN when applied to patients with STEMI was 0.57 [14] which is much lower than the performance of our score. Most importantly, AKI in the setting of myocardial infarction is multifactorial and should not be assumed to be solely a contrast-induced nephropathy, as demonstrated by Shacham et al [5,6]. Therefore, the use of these scores cannot be extended to predict AKI in AMI patients.…”
Section: Discussionmentioning
confidence: 99%
“…AKI in the setting of AMI is a multifactorial entity [5]. Beyond the widely recognized negative impact of contrast volume, the key mechanisms in AKI pathogenesis include systemic and renal hemodynamic changes secondary to impaired cardiac output, arrhythmias, and increased venous congestion [1,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this group, AKI is associated with contrast volume, hemodynamic impairment, inflammation, bleeding, and nephrotoxic agents [1, 3, 4]. However, the incidence of AKI reported varies considerably with the population evaluated and the definitions used [1, 6].…”
Section: Introductionmentioning
confidence: 99%
“…Marenzi et al found that lower LVEF is associated with CIN 36. Cowburn et al found that patients developing CRP were independent risk factors for CIN [38][39][40]. Moreover, in the Mehran score, diabetes mellitus, congestive heart failure, CM volume, age >75 years, and IABP usage are recognized as risk factors for mortality 41.…”
mentioning
confidence: 99%